Taṭwīr Mawādd Mahārat al-Qirā'ah al-Qā'imah ʿalā al-Tarbiyah al-Akhlāqiyyah bi al-Dhakā' al-Iṣṭināʿī - Wiwik Prasetiyo Ningsih; M. Abdul Hamid; Abdul Wahab Rosyidi; Qur’ani Parang Wilwadikta (Al-Wazan: Journal of Arabic Education, 2026)
Teaching reading skills requires teachers to develop innovative instructional materials that respond to learners’ academic and moral needs. At the Institute of Dar al-Lughah wa al-Qur’an, students experienced difficulties in reading Arabic texts accurately, demonstrated limited vocabulary mastery, and relied on conventional learning materials that lacked attractive and interactive features. Moreover, several ethical problems, including bullying and mockery among students, highlighted the need to integrate character education into reading instruction. Therefore, this study aimed to develop artificial intelligence-assisted reading materials based on moral education, identify the characteristics of the developed product, and evaluate its effectiveness in improving students’ reading skills and moral awareness. The study employed a mixed-methods research and development approach using the Borg and Gall ten-stage model. Data were collected through observations, interviews, tests, questionnaires, and documentation. Qualitative data were analyzed using classificatory analysis, while quantitative data were examined using the t-test. The developed product consists of moral-based reading texts, AI-supported multimedia content, vocabulary songs employing musical mnemonic techniques, interactive reading exercises, and Google Sites integration for easy access. The materials emphasize moral values such as honesty, discipline, responsibility, respect, and social care through contextual stories, multimedia learning, simplified language, child-friendly digital design, and interactive assessments with immediate feedback. The findings demonstrate that the product significantly improved students’ reading achievement, with t₀ = 20.98 exceeding the critical values at both the 0.01 and 0.05 significance levels. Furthermore, interviews revealed that 76% of students reported increased motivation to practice positive behaviors after engaging with the materials. This study contributes a novel AI-assisted moral education framework that simultaneously enhances Arabic reading proficiency and character development in primary Islamic education.